Separate cortical and hippocampal cell populations target the rat nucleus reuniens and mammillary bodies. (21st February 2019) - Mathiasen, Mathias L.; Amin, Eman; Nelson, Andrew J. D.; Dillingham, Christopher M.; O'Mara, Shane M.; Aggleton, John P.
Abstract: Nucleus reuniens receives dense projections from both the hippocampus and the frontal cortices. Reflecting these connections, this nucleus is thought to enable executive functions, including those involving spatial learning. The mammillary bodies, which also support spatial learning, again receive dense hippocampal inputs, as well as lighter projections from medial frontal areas. The present study, therefore, compared the sources of these inputs to nucleus reuniens and the mammillary bodies. Retrograde tracer injections in rats showed how these two diencephalic sites receive projections from separate cell populations, often from adjacent layers in the same cortical areas. In the subiculum, which projects strongly to both sites, the mammillary body inputs originate from a homogenous pyramidal cell population in more superficial levels, while the cells that target nucleus reuniens most often originate from cells positioned at a deeper level. In these deeper levels, a more morphologically diverse set of subiculum cells contributes to the thalamic projection, especially at septal levels. While both diencephalic sites also receive medial frontal inputs, those to nucleus reuniens are especially dense. The densest inputs to the mammillary bodies appear to arise from the dorsal peduncular cortex, where the cells are mostly separate from deeper neurons that project to nucleus reuniens. Again, in those other cortical regions that innervate both nucleus reuniens and the mammillary bodies, there was no evidence of collateral projections. The findings support the notion that these diencephalic nuclei represent components of distinct, but complementary, systems that support different aspects of cognition. Abstract : We compared the sources of inputs to nucleus reuniens and the mammillary bodies. Retrograde tracers showed how these sites receive projections from separate cell populations, often from adjacent layers. In the subiculum, dense mammillary inputs (red) originate from pyramidal cells located at more superficial levels than those cells (often polymorphic) that target nucleus reuniens (blue). Similar laminar differences occur in frontal cortices, where inputs to reuniens are considerably denser.